2016
DOI: 10.1136/rmdopen-2015-000137
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of tocilizumab in giant cell arteritis and large vessel vasculitis

Abstract: Giant cell arteritis (GCA) is a chronic systemic vasculitis affecting large-sized and medium-sized vessels. Glucocorticoids are currently the mainstay of treatment for GCA and associated large vessel vasculitis (LVV) but are associated with frequent adverse events. Methotrexate has only demonstrated a modest benefit while anti-TNF biological agents (infliximab and etanercept) have been inefficacious. Elevated levels of interleukin-6 (IL-6), a proinflammatory cytokine, has been associated with GCA. Tocilizumab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 16 publications
0
26
0
4
Order By: Relevance
“…[14] Indeed, several open-label studies using TCZ reported remission and maintenance thereof in refractory GCA patients. [12,13,15,42,43] However, serious side effects including neutropenia, hepatitis, and infections were reported in these studies in up to 27%, and death occurred in 3 patients. Furthermore, data on the frequency of relapses after TCZ withdrawal are lacking in these studies.…”
Section: Discussionmentioning
confidence: 98%
“…[14] Indeed, several open-label studies using TCZ reported remission and maintenance thereof in refractory GCA patients. [12,13,15,42,43] However, serious side effects including neutropenia, hepatitis, and infections were reported in these studies in up to 27%, and death occurred in 3 patients. Furthermore, data on the frequency of relapses after TCZ withdrawal are lacking in these studies.…”
Section: Discussionmentioning
confidence: 98%
“…Rituximab is a synthetic antibody that selectively reduces the number of B cells circulating in the blood, and it helps to decrease inflammation without the use of steroids. A humanized anti‐human IL‐6 receptor antibody tocilizumab has been successfully used and in eight cases of refractory large‐vessel vasculitis and CGA . Mepolizumab, an anti‐IL‐5 monoclonal antibody that binds to IL‐5 and prevents its interaction with its receptor on the eosinophil surface, has been used in the treatment of eosinophilic granulomatosis with polyangiitis (Churg‐Strauss syndrome) …”
Section: Concluding Remarks and Therapeutic Perspectivementioning
confidence: 99%
“…A más intéz-ményben végzett sürgősségi vizsgálatok során -mellkasröntgenen, koponya CT-n -kóros nem volt. Laboratóri-umi leleteiből magas C-reaktív protein (196 mg/L) és Westergreen-érték (70 mm/h), leukocytosis (11,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)5 G/L) emelhető ki. Sürgősséggel elvégzett anti-DNS-, anti-MPO-, anti-PR3-, anti-GBM-antitest-vizsgálatok és antifoszfolipidantitest-vizsgálatok negatívak lettek.…”
Section: Esetismertetésunclassified
“…A citosztatikumok kedvező hatását nem sikerült bizonyítani [2,4,12]. A biológiai terápiákkal kapcsolatban egyelőre kevés és kis betegszámú vizsgálat, csekély tapasztalat áll rendelkezésre, tocilizumabbal történt kis betegszámú vizsgálatok során biztató eredmények láttak napvilágot [13].…”
Section: Táblázat)unclassified